(untitled) (Research, Society and Development, 2021)
Orotracheal intubation (OTI) is a procedure indicated when there is a need for definitive airway control. Since OTI is performed in emergency situations, such as in cardiac arrest, there are few contraindications to the procedure, one of the main ones being partial tracheal transection. The chance of success in performing OTI by medical students increases by 9% with each attempt (OR 1.09; 95% CI 1.04 - 1.14), requiring at least 17 attempts of OTI to have a 90% success rate. Thus, the aim of this cross-sectional study is to evaluate medical students’ knowledge about orotracheal intubation. It was observed that more than 90% of the respondents reported knowing why OTI is performed; however, only 67.1% and 53.2% know the indications and contraindications for performing OTI, respectively. 92.4% of the participants reported knowing about Mallampati’s classification, however 82.3% reported that they know how to recognize an airway that is difficult to intubate. It was found that recently graduated or internship students reported having more knowledge about the reason to perform OTI (p=0.04), materials needed for OTI (p=0.04), Mallampati classification (p<0.01) and recognition of a difficult to intubate airway (p=0.04) when compared to students in basic or clinical stage. Although it is a limited study due to its cross-sectional methodology, some gaps in knowledge can be observed, for example only 59.5% of the participants reported knowing the complications that can be caused by OTI.